2014
DOI: 10.1016/j.cellsig.2014.02.023
|View full text |Cite
|
Sign up to set email alerts
|

KIBRA: In the brain and beyond

Abstract: In mammals, the KIBRA locus has been associated with memory performance and cognition by genome-wide single nucleotide polymorphism screening. Genetic studies in Drosophila and human cells have identified KIBRA as a novel regulator of the Hippo signaling pathway, which plays a critical role in human tumorigenesis. Recent studies also indicated that KIBRA is involved in other physiological processes including cell polarity, membrane/vesicular trafficking, mitosis and cell migration. At the biochemical level, KI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 84 publications
1
74
1
Order By: Relevance
“…The mechanism/s by which these two polymorphisms (KIBRA rs17070145, CLSTN2 rs6439886) may influence episodic memory functioning is unclear. KIBRA encodes a phosphoprotein, which binds to many proteins including those implicated in neuronal and synaptic plasticity, cell migration, vesicular transport, mitosis and tumorigenesis (Zhang et al, 2014). It has been proposed that KIBRA regulates AMPA receptors, the major excitatory synaptic receptors of the brain, suggesting KIBRA may be involved in synaptic plasticity and transmission (Makuch et al, 2011;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism/s by which these two polymorphisms (KIBRA rs17070145, CLSTN2 rs6439886) may influence episodic memory functioning is unclear. KIBRA encodes a phosphoprotein, which binds to many proteins including those implicated in neuronal and synaptic plasticity, cell migration, vesicular transport, mitosis and tumorigenesis (Zhang et al, 2014). It has been proposed that KIBRA regulates AMPA receptors, the major excitatory synaptic receptors of the brain, suggesting KIBRA may be involved in synaptic plasticity and transmission (Makuch et al, 2011;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Both KIBRA and CLSTN2 are highly expressed in the medial temporal lobe (Zhang et al, 2014;Schneider et al, 2010;Hintsch et al, 2002), a brain region important for episodic memory (Squire, Stark, & Clark, 2004). Moreover, it has been shown that in the Older Australian Twins Study and other cohorts that ~53-65 % of the variance in hippocampal volume can be attributed to genetic influences (Blokland, de Zubicaray, McMahon, & Wright, 2012;Mather et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it was reported that KIBRA interacts with discoidin domain receptor 1 and modulates collagen-induced extracellular signal-regulated kinase (ERK) signaling in normal breast cells (13). KIBRA also functions as an adaptor protein that exercises its functions by interacting with other proteins (14).…”
mentioning
confidence: 99%
“…By contrast, rs10038727, the SNP found to be associated with PTSD (6,7), is located much closer to the regions encoding the PKMζ interaction site. Zhang et al (11) highlighted the existence of an exonic mutation at this site, which most likely influences PKMζ binding affinity (11) and only maps approximately 1000 base pairs from rs10038727. On the other hand, rs10038727, despite being an intronic variant, could be functional itself by altering transcription factor binding sensitivity (6).…”
mentioning
confidence: 99%